Climate Change and Social Protection in Bangladesh: Are Existing Programmes Able to Address the Impacts of Climate Change?. (10th October 2013) - Coirolo, Cristina; Commins, Stephen; Haque, Iftekharul; Pierce, Gregory
Abstract : Bangladesh is generally considered to be one of the most disaster‐prone countries in the world, with flooding, droughts and cyclones being the most common annual disaster events. This article provides an overview of existing social‐protection programmes and government policies in the context of long‐term adaptation to climate change related to sudden onset disasters, and evaluates their effectiveness in addressing related vulnerabilities and promoting food security in climate‐vulnerable regions in the country.